INDONESIAN RED CROSS ASSOCIATION - Kesi; Usiono; Amri; Yunita Syahfitri (CV. Asry Persada Quality, 2025)
Disaster preparedness is an important element in minimizing the negative impacts on the community. The Indonesian Red Cross Association (PMI) has a vital role in helping the community prepare for potential disasters through a number of mitigation programs. This study aims to analyze the strategies implemented by PMI in improving community preparedness, evaluating the level of success of the implementation of these programs, and assessing their impact. The approach used in this study is descriptive qualitative, with data collection through interviews, observations, and document analysis. The results show that PMI has succeeded in educating the community through training, disaster simulations, and capacity building programs at the local level, although it is still faced with challenges of limited funds and manpower. Therefore, there needs to be stronger collaboration between PMI and the government to strengthen the effectiveness of disaster preparedness programs.learning.